Kajian Kriminologi Terhadap Kekerasan Yang Dilakukan Oleh Perempuan di Kota Ambon - Denny Latumaerissa (Criminal of Law Department, Faculty of Law, Pattimura University, 2020)
Essentially violent crime can occur wherever, anytime, and can be done by anyone without any distinction sex. That is guilty can male or female. The reality that occurs suggests that female also often perpetrated a violent crimes. Such as happened in the city of Ambon, which according to the data from Polresta P.Ambon and P. P lease, suggests that from 2017 until 2019, there are 14 ( fourteen ) violence made by women on jurisdiction. That has been a problem in writing this is what has been factor-factor cause violence carried out by women in the city ambon. Factors influencing the so that a woman committed violence in the city of Ambon is the family, the motivation, / sexual disorder of sexual perversion, and the role of the victim